Embracing Metaverse towards Sustainable Tourism in Oman - Al-Azri, Abdullah Khalfan; Jetti, Edukondala Rao; Ramachandran, Nithya (Journal of Ecohumanism, 2024)
The metaverse, a digital environment linking augmented and virtual reality technologies, is an evolving tool for transformation across industries. This conceptual paper explores the potential of a metaverse in revolutionizing Oman’s tourism landscape. Leveraging metaverse in tourism sector can help Oman in achieving its sustainable development goals. This paper discusses the role of a metaverse in designing inclusive and innovative tourism experiences while addressing the challenges of resource management, cultural conservation, and over-tourism. This paper is developed by reviewing a wealth of relevant literature to explore the implications of metaverse on sustainable tourism in Oman. It is an attempt to make Oman’s rich heritage, culture and natural beauty accessible to global travellers and strengthen Oman’s potential to market its tourism attractions to global tourists. The paper proposes suggestions to policy makers on the strategic initiatives with regard to integrating metaverse-driven solutions in Oman’s tourism industry for achieving the goals of social and economic sustainability aligned with its Vision 2040.